Contemporary management of skin cancer – dermatology, surgery or radiotherapy? - Chicheł, Adam; Skowronek, Janusz (Contemporary Oncology/Współczesna Onkologia, 2005)
Skin cancer is the most common malignancy in a human. Taking under consideration their frequent occurrence and serious cosmetic defects they tend to be a significant clinical problem if not treated, thus decreasing the quality of life of the patients. The aim of this study was to present basic information on biology, symptoms and management of skin cancers. Histology and epidemiology of skin cancers have been discussed and particular attention has been paid to basal cell and squamous cell carcinomas (BCC and SCC), which make together 95 percent of primary malignancies of the skin. Present medical literature has been overviewed and data related to therapeutic methods used in dermatology, surgery, teleradiotherapy (EBRT) and brachytherapy (BT) have been collected. Characteristics, long-term outcomes, cosmetic and side effects of particular therapeutical strategies are described.